A Descriptive Review of the Role of Epidemiological Data in Public Health Policy Formulation - Azzah, Farhanah Naurah; Muhammad Aqasyah Arya (Science Publication: Journal of Public Health and Nutrition, 2025)
ABSTRACT This study aims to provide a descriptive qualitative review of the role of epidemiological data in formulating public health policies, focusing on its function as a foundation for evidence-based and equitable decision-making. Using a qualitative-descriptive research design through a literature-based study, data were collected from peer-reviewed journals, official reports, and theoretical frameworks published between 2011 and 2025. The analysis was conducted through stages of data reduction, thematic categorization, and inductive interpretation to identify patterns in how epidemiological evidence supports public policy development. The findings reveal that epidemiological data play a critical role in five major domains: early detection and surveillance, identification of risk factors, evaluation of interventions, reduction of health inequalities, and enhancement of research-policy collaboration. These results indicate that effective policymaking depends on the integration of epidemiological evidence within structured frameworks such as evidence-informed policymaking and output-oriented policy engagement. Furthermore, the study highlights that epidemiological data not only improve efficiency and responsiveness in health governance but also promote fairness by identifying and addressing social and regional disparities in health outcomes. Despite challenges related to data accessibility, standardization, and interdisciplinary coordination, the research concludes that strengthening the use of epidemiological data is essential for achieving adaptive and just health policies. The study contributes theoretically by reinforcing the linkage between epidemiological research and policy design, and practically by outlining strategies for data-driven governance in public health. Keywords: Epidemiological data, public health policy, evidence-based decision-making, health equity, qualitative descriptive study,